Sustainability of Goa Tourism - Perception of Tourists: Examining the Factors Influencing Sustainable Tourism in Goa (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research paper attempts to examine the economic, social, and environmental sustainability of Goa tourism and the factors that determine the sustainability of tourism development in Goa. Descriptive statistics and factor analysis are two methods used to examine the sustainability of tourism development. The descriptive statistics establish that tourism development is contributing to the economic and environmental sustainability of Goa. However, tourism has caused unfavorable impacts on the social and cultural environment of Goa. The factor analysis establishes that resource exploitation, resource management, environment management, destination unsustainability, economic sustainability, local sustainability, tourism governance, community engagement, and socio-cultural sustainability influence the sustainability of tourist destinations in Goa.